Video comprehension in e-learning: Effects of note taking, video format, and working memory - Marrujo Sucno, Jonathan Gabriel (2023)
This study examined spontaneous note-taking when studying from expository texts and videos in an experimental remote E-learning environment. Two hundred and ten undergraduates read texts, or watched videos with different cognitive load, to answer comprehension questions, followed by a self-report strategic questionnaire about the tasks previously completed; working memory was assessed face-to-face. The proportion of students who adopted a particular strategy, and specifically, the proportion who took notes, did not significantly vary as a function of presentation format. Strategy contributed to comprehension; compared to passively reading or watching the videos, taking notes significantly improved performance. The efficacy of note-taking did not vary as a function of presentation format, type of video, or working memory capacity. Overall, this study shows that in an e-learning setting, note-taking for digital text and video online expository comprehension is adopted spontaneously by around 40 % of college students, and is equally effective for all formats of instruction. This result is relevant for theories of multimedia comprehension, as well as for applied educational settings.